A God of Mockery? Revisiting the “Omnipotence Effect” in Numbers 22:21–35 - Kanasiro, André (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2024)
The characterization of YHWH, Israel's only God, is unique in the Hebrew Bible. The deity, while a character in the narrative, transcends the narrative on the level of discourse, rising above other characters, the narrator, and even the reader. This exceptional dynamic of characterization is exemplarily illustrated in the episode of Balaam and the talking jenny (Num 22:21–35), a text loaded with irony and ambiguity that recounts the deliverance of a foreign seer from YHWH’s hands by his jenny. The characterization of YHWH in this text shows a God who manipulates both the narrated world and the formal structure of the text, exemplifying what Sternberg termed the “omnipotence effect.”